CNDOمعالجة كمية للتوزيع الالكتروني لجزيئة الماء باستعمال طريقة الاهمال التام للتداخل التفاضلي - ابراهيم عبود حامد; محمد عبد الجليل حيدر; موجد شياع قيس; هاشم هادي نضال (University of Thi-Qar Journal of Science, 2009)
The electronic distribution of water molecule is studied theoretically in this work, using the complete Neglect of differential overlap (CNDO) semi empirical method. The wave functions used to describe this system are of the type STO-3G depends on the Hartree-Fock equations for restricted systems. The calculations contains the geometry optimization, total energy of the molecule in a.u, the eigenvalues and eigenfunctions ( atomic orbital coefficients). A good accuracy appears from comparing the results with respect to numerical methods. In addition that this method is quicker than of the numerical methods.